Modeling Using Box Behnken Design for Optimization of Biodiesel Production from Low Grade Cooking Oil - Zulkurnain, Nursyamimi; Ahmad, Aisyah Fathiah; Mat Rosid, Salmiah Jamal; Azid, Azman; Toemen, Susilawati (Vietnam Journal of Science and Technology, 2024)
The demand to an alternative for the depletion of diesel oil, has steered to the production of biodiesel as an alternative fuel. Nowadays, there is a growing need for biodiesel, which is typically produced using a base-catalyzed transesterification reaction. Therefore, this research utilizing a low-grade cooking oil as the biodiesel feedstock and Ca/Mg/Al2O3 as a heterogenous base catalyst using wetness impregnation method. The potential catalyst was optimized using response surface methodology (RSM) by varying parameters of calcination temperature, catalyst dosage and reaction time. The optimum parameter obtained from the RSM are 800°C calcination temperature, 6wt% catalyst dosage and 1 hour reaction time. The validation is carried out using optimum parameter and it gave 48.30% of biodiesel production.